On-farm leaf curl disease management of chilli (Capsicum annuum L.) - Pandey, R.; Chaturvedi, A. K.; Chaudhary, R. P.; Prasad, R. (Journal of Phytopathology and Disease Management, 2017)
Chilli is an important vegetable and condiment used widely in Indian food preparations. Chilli leaf curl caused by chilli leaf curl virus transmitted by whiteflies is one of the major limiting factors in cultivation of the crop. Two different integrated disease management practices were compared with regular farmer conventional practices (sole reliance upon chemicals). Field experiments were conducted for the disease management of leaf curl in chilli including seed treatment with imidacloprid 17.8% at the rate 3 g kg-1 of seed, seedling treatment with imidacloprid 17.8% at the rate 0.3 ml l-1 of water for 30 minutes and destruction of infested plants and foliar sprays of imidacloprid at the rate 0.3 ml l-1 of water during two successive years i.e. 2012 and 2013. There was 41 to 74% protection, against disease incidence, observed over conventional practices based solely on use of chemicals. However, IDM practices fairly restricted the leaf curl index from 2.2 to 0.8 and an increased advantage 5.78 to 18.34% yield over farmers’ practice. Number of foliar sprays of insecticides was also reduced to a great extent from 10 to 4. Besides, highest benefit cost (B:C) ratio 3.66 to 3.74 was recorded under integrated disease management practices against 3.04 to 3.09 under farmers’ practice.